2020
DOI: 10.4314/jasem.v24i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Response Surface Methodology and Artificial Neural Network for Modeling and Optimization of Extraction Process Parameters on <I>Tetrapleura Tetraptera</I>

Abstract: Bioactive compounds in the fruits of Tetrapleura tetraptera is widely used in food as a flavouring agent and for spices. In this study, bioactive compounds were extracted by solid-liquid extraction process and the yield was optimized by response surface methodology (RSM) and artificial neural network (ANN). The process parameters optimized were the extraction temperature, particle size and extraction time. Box-Behnken Design was used to study the effect of the process parameters on the extract yield. A quadrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Cyclopentadecanone, 2-hydroxy-merupakan golongan komponen penyusun minyak atsiri [30] dan memiliki aktivitas antimikroba [31].…”
Section: Komposisi Kandungan Minyak Kulitunclassified
“…Cyclopentadecanone, 2-hydroxy-merupakan golongan komponen penyusun minyak atsiri [30] dan memiliki aktivitas antimikroba [31].…”
Section: Komposisi Kandungan Minyak Kulitunclassified
“…Antibacterial activity has been reported in 9-octadecenamide, (Z)-; beta-amyrin); .gamma. -Linolenic acid, methyl ester; dehydroabietylamine; longifolene; 1,2-benzenedicarboxylic acid, diethyl ester (Ghosh et al 2021); cyclopentadecanone, 2-hydroxy- (Oyedoh et al 2020); dehydroabietic acid and its TMS derivative (Fukui et al 1978); pentafluoropropionic acid, heptadecyl ester (Pandey et al 2011); phenol (Nwosu et al 2022); stigmasterol (Vida et al 2012); Antimicrobial property was observed in 13-hexyloxacyclotridec-10-en-2one (Malayaman et al 2019); longifolene; 1,2benzenedicarboxylic acid, diethyl ester; 1,4-dimethyl-3-(2methyl-1-propenyl)-4-vinyl-1-cycloheptene (Ghosh et al 2021). Activities against fungal isolates were reported in beta-amyrin (Ghosh et al 2021); dehydroabietic acid and its TMS derivative (Feio et al 1999); dehydroabietylamine; 13-hexyloxacyclotridec-10-en-2-one; ethanone, 1-phenyl-; 1,2-benzenedicarboxylic acid, diethyl ester (Ghosh et al 2021).…”
Section: Effect Of Extracts From Shade Tree Litter On Psm Growthmentioning
confidence: 99%
“…RSM (Response Surface Methodology) and ANN (Artificial Neural Network) models are commonly employed for data analysis and prediction in optimization experiments across various domains, such as food [ 18 , 19 ] and materials [ 20 , 21 ]. The RSM model utilizes a second-order polynomial model: to study the relationship between one or more response variables and a number of independent variables, allowing for intuitive analysis of the influence of experimental factors on the results [ 22 , 23 ]. Central composite, Doehlert and Box-Behnken are three main response surface design methods [ 24 , 25 ] where Box-Behnken design is based on the multivariate optimization technique of three-level incomplete factorial design, which, due to its absence of axial points, helps to reduce the cost of the experiment and the number of experimental runs number of times, allowing experiments to be done more efficiently and economically [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%